2014
DOI: 10.2478/acve-2014-0047
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Cat Leptospirosis in Belgrade (Serbia)

Abstract: With its epizootiological characteristics, the territory of the municipality of Belgrade city is a potentially important locality for the maintenance and spreading of a number of serovars of Leptospira interrogans. In order to evaluate the epizootiological situation as far as animal leptospirosis in the Belgrade region is concerned, from January 2012 until June 2013 the prevalence of cat leptospirosis has been evaluated. The standard microagglutination test (MAT) was used to determine animals sero positive to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 16 publications
0
11
1
3
Order By: Relevance
“…Serologically, 25.6% (n = 21/82) of the cats had positive antibody titers (100-1,600) against the pathogenic serogroups, namely Bataviae, Javanica, and Ballum. Cats in this study had higher leptospiral serodetection compared to that of other recent cats studies in the USA, Brazil, Iran, Canada, Taiwan, and Germany, which ranged between 4.8% and 17.9% [11][12][13][14][31][32][33][34], but lower serodetection compared to those reported in Greece and Serbia, which ranged between 26% and 33% [35,36]. MAT test results may vary because of the serovar panel used in the geographical area of interest and the cut-off value.…”
Section: Discussioncontrasting
confidence: 53%
“…Serologically, 25.6% (n = 21/82) of the cats had positive antibody titers (100-1,600) against the pathogenic serogroups, namely Bataviae, Javanica, and Ballum. Cats in this study had higher leptospiral serodetection compared to that of other recent cats studies in the USA, Brazil, Iran, Canada, Taiwan, and Germany, which ranged between 4.8% and 17.9% [11][12][13][14][31][32][33][34], but lower serodetection compared to those reported in Greece and Serbia, which ranged between 26% and 33% [35,36]. MAT test results may vary because of the serovar panel used in the geographical area of interest and the cut-off value.…”
Section: Discussioncontrasting
confidence: 53%
“…In this study, we found 37% (cut-off 1:40) of seroprevalence for Leptospira infection, which is close to the only study published regarding the cat population in the island at that time that reported 26.6% (cut-off titre 1:100) [ 15 ]. When looking at studies performed in other countries published over the last 5 years, the mean seroprevalence observed in cats was 14%, with only one study with a prevalence over 20% in Serbia (cut-off titre 1:100) [ 11 , 13 , 16 , 19 , 26 31 ]. Our study records a high seroprevalence in cats, which could be due to a lower cut-off value (1:40).…”
Section: Discussionmentioning
confidence: 99%
“…Leptospirosis is an example of this dynamic interface with wildlife [41]. Serovars belonging serogroups Australis, Autumnalis, Batavie, Bratislava, Grippotyphosa, and Pomona have been previously described in cats from Europe [12,15,16,27,39,42].…”
Section: Discussionmentioning
confidence: 99%